Mitochondrial oxidative stress, mitochondrial ROS storms in long COVID pathogenesis - Noonong, Kunwadee; Chatatikun, Moragot; Surinkaew, Sirirat; Kotepui, Manas; Hossain, Rahni; Bunluepuech, Kingkan; Noothong, Chanittha; Tedasen, Aman; Klangbud, Wiyada Kwanhian; Imai, Motoki; Kawakami, Fumitaka; Kubo, Makoto; et al. (Frontiers in Immunology, 2023)
Significance: This review discusses the coronavirus disease 2019 (COVID-19) pathophysiology in the context of diabetes and intracellular reactions by COVID-19, including mitochondrial oxidative stress storms, mitochondrial ROS storms, and long COVID. Recent Advances: The long COVID is suffered in ~10% of the COVID-19 patients. Even the virus does not exist, the patients suffer the long COVID for even over a year, This disease could be a mitochondria dysregulation disease. Critical Issues: Patients who recover from COVID-19 can develop new or persistent symptoms of multi-organ complications lasting weeks or months, called long COVID. The underlying mechanisms involved in the long COVID is still unclear. Once the symptoms of long COVID persist, they cause significant damage, leading to numerous, persistent symptoms. 4 This is a provisional file, not the final typeset article Future Directions: A comprehensive map of the stages and pathogenetic mechanisms related to long COVID and effective drugs to treat and prevent it are required, which will aid the development of future long COVID treatments and symptom relief.